Perencanaan Keuangan Pribadi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Papua - Usman, Sarah; Suruan, Ted (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This research was conducted at the Faculty of Economics and Business, the University of Papua to examine the effect of each variable on personal financial planning. Respondents in this study were 290 students whose sampling technique was proportional stratified random sampling using a quantitative approach. The results of learning research in higher education are influential. Meanwhile, financial management education in the family, self-control, and income do not affect student financial planning. For this reason, students must have the intention/willingness and have clear financial goals to achieve predetermined financial goals.